Reperspectivization in Translating News of Trump Statement Wants to Take Over Gaza - Rizki Gunawan (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
The BBC English news story titled "Why does Trump want to take over Gaza and could he do it?" was translated to the BBC Indonesia page with the headline "Mengapa Trump ingin mengambil alih Gaza dan dapatkah dia melakukannya?". This research is aimed at investigating Reperspectivization as one of the procedures commonly employed on the BBC news translation. This analyzed how the text was translated by the translation journalist on the smallest units of words, sentences, and paragraphs, progressing to the context, thoughts, and ideologies by using text analysis method of Critical Discourse Analysis (CDA) theory by Norman Fairclough's. It was found that Reperspectivization procedure is quite dominant in translating this text with some types: passive to active, part – another part, reversal of terms, negation of opposite, concrete for abstract, and change of symbol. The translation journalist also implemented the text relocation and addition of Ministry of Foreign Affair of Republic of Indonesia response on Donald Trump statement that shows that domestic viewpoints have a significant influence on the news translation.